Theoretical and Experimental Study of Comb-Actuated Mirror with Cascaded Structures - Wenhao Chen; Huahuang Luo; Mingzheng Duan; Hadi Tavakkoli; Wibool Piyawattanametha; Yi-Kuen Lee (My University, 2023)
For the first time, we present a two-dimensional theoretical model for one-dimensional comb-actuated MEMS mirror with cascaded structures. The numerical model including different damping mechanisms and nonlinear capacitive force is validated with experiment results. Stability analysis is conducted to simulate the nonlinear hysteretic frequency response. The model proposed can be a guideline for designing multi-degree-of-freedom nonlinear parametric-excited MEMS mirror with high frequency and large scan angle.
Keywords: Advanced MEMS and NEMS Technologies; Advanced Fiber Optic Sensors; Photonic and Optical Devices